2017
DOI: 10.1210/js.2017-00006
|View full text |Cite|
|
Sign up to set email alerts
|

F2-Isoprostanes Reflect Oxidative Stress Correlated With Lean Mass and Bone Density but Not Insulin Resistance

Abstract: Context:F2-isoprostanes (F2-isoPs) are biomarkers for oxidative stress in humans and have been shown to be elevated in obesity, cardiovascular disease, and diabetes. Therefore, F2-isoPs are often implicated in oxidative stress contributing to insulin resistance, although this has not been rigorously examined.Objective:To determine whether urinary F2-isoPs are predictive of insulin sensitivity and other clinical metabolic parameters.Participants:Sedentary, weight-stable, nondiabetic adults equilibrated on a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 42 publications
3
19
1
Order By: Relevance
“…It has been found that iso-PGE 2 but not iso-PGF 2 alpha had an inhibitory effect on the induction of alkaline phosphatase activity in MC3T3-E1 preosteoblasts [42]. Urinary F2-isoprostanes levels have been found to show a negative correlation with bone mineral content and bone mineral density [43]. It has been found that patients with diabetes, obesity, hypercholesterolemia, smokers, etc., have higher levels of urinary isoprostane [44].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that iso-PGE 2 but not iso-PGF 2 alpha had an inhibitory effect on the induction of alkaline phosphatase activity in MC3T3-E1 preosteoblasts [42]. Urinary F2-isoprostanes levels have been found to show a negative correlation with bone mineral content and bone mineral density [43]. It has been found that patients with diabetes, obesity, hypercholesterolemia, smokers, etc., have higher levels of urinary isoprostane [44].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Elharram et al, (2017) and Raefsky et al, (2018) demonstrated that deuterium-reinforced PUFAs (D-PUFA) are more resistant to lipid peroxidation mediated by ROS in comparison with regular hydrogenated PUFAs [ 221 ] and that in mouse models of cognitive impairment, with AD-like biochemical and structural pathologies, treatment with D-PUFA for 18 weeks showed a strong effect in the hippocampus and cortex. An approximate 55% reduction of F2-isoprostanes [ 222 ], which are biomarkers for OS in humans and are elevated in obesity [ 223 ], was observed. Moreover, prostaglandin F2α was reduced [ 217 ] and this compound is associated with neuropsychiatric and neurologic disorders [ 224 ].…”
Section: The Therapeutic Potential Of Other Fatty Acid In Ndsmentioning
confidence: 99%
“…Moreover, the Framingham cohort study showed that urinary inflammation and oxidative stress (total isoprostane) parameters were inversely associated with total protein and plant protein [ 28 ]. Further, a cross-sectional study on healthy youth with weight stable for three months and an isocaloric diet (50% carbohydrate, 30% fat, 20% protein), reported no association between urinary 15-F 2t -IsoP and basal carbohydrate and lipid oxidation rate [ 29 ]. Contrary to the current study, no differences were demonstrated in consumption of total energy, carbohydrate, protein and fat between different quartiles of F 2 -isoP in a cross-sectional study among postmenopausal women [ 30 ].…”
Section: Discussionmentioning
confidence: 99%